On The Analysis Of Mcm Systems Papr Profiles And The Wp-Ofdm System Papr Reduction Techniques - Zakaria, Jamaluddin (2013)
Orthogonal frequency division multiplexing (OFDM) is a prominent system in transmitting multicarrier modulation (MCM) signals over selective fading channel. It has several magnificent properties such as attaining a higher degree of bandwidth efficiency, higher data transmission, robust to narrowband frequency interference and low-complexity implementation. However, the system has its shortage which needs improvement; high peak-to-average power ratio (PAPR) where the signals work in the nonlinear region of the high power amplifier (HPA) results in poor performance and other signal property impairments. Apart from that, an attractive dynamic tool which is wavelet analysis is utilized, and its derivatives such as wavelet packet transform (WPT) possesses almost the same criteria of the orthogonal Fourier base MCM system. Wavelet base analysis surpasses Fourier base by inherent flexibility in terms of windows function for non-stationary signal analysis. The subset base of WPT known as discrete wavelet transforms (DWT). In MCM system, these two base functions construct the orthogonal modulation signal system as the fast Fourier transform (FFT) do in the conventional OFDM (COFDM) system. Applying both WPT and DWT in the MCM system, produces orthogonal signals known as the wavelet packet-based OFDM (WP-OFDM) and wavelet-based OFDM (WOFDM) signals respectively. With no cyclic prefix (CP) need to be applied, these orthogonal signals hold higher bandwidth efficiency. Hence, a comprehensive study is established by performing manipulation on specified parameters using WP-OFDM, WOFDM and C-OFDM signals under the additive white Gaussian noise (AWGN) channel. Furthermore, Partial Transmit Sequence (PTS) is an efficient technique to mitigate the large PAPR in WP-OFDM signals.